Efficiency of emerging forex markets during the American and European quantitative easing periods - Stevens, Darion (My University, 2020)
This research report investigated the efficiency of BRICS country foreign exchange markets during the American and European Quantitative Easing (QE) Periods. Market efficiency tests included autocorrelation, unit root, variance ratio, co-integration, and uncovered interest parity (UIP) testing. UIP tests indicated that the currency pairs investigated are not strong form efficient and that market efficiency diminished for US cross pairs during QE. The research also highlights changes in efficiency state prior to and post QE for the cross-pairs studied.
A research report submitted in fulfilment of the requirements for the degree of Masters of Management in Finance and Investment (MMFI) to the Faculty of Commerce, Law and Management, Wits Business School, University of the Witwatersrand, Johannesburg, 2020
Keywords: Forex; Forex markets; EUROPEAN; AMERICAN; BRICS; Foreign exchange; American and European Quantitative Easing; SDG-8: Decent work and economic growth